2018
DOI: 10.1016/j.molcel.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Regulation of METTL16, an S-Adenosylmethionine Homeostasis Factor

Abstract: S-adenosylmethionine (SAM) is an essential metabolite that acts as a cofactor for most methylation events in the cell. The N-methyladenosine (mA) methyltransferase METTL16 controls SAM homeostasis by regulating the abundance of SAM synthetase MAT2A mRNA in response to changing intracellular SAM levels. Here we present crystal structures of METTL16 in complex with MAT2A RNA hairpins to uncover critical molecular mechanisms underlying the regulated activity of METTL16. The METTL16-RNA complex structures reveal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
272
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(285 citation statements)
references
References 48 publications
11
272
2
Order By: Relevance
“…METTL16 binds a subset of mRNAs and methylates long noncoding RNA (lncRNA) and U6 small nuclear RNA (U6 snRNA) [59,60]. The UACAGAGAA sequence is required for METTL16-mediated-methylation and the Nterminal module of METTL16 is essential for RNA binding [61,62].…”
Section: Mettl16mentioning
confidence: 99%
“…METTL16 binds a subset of mRNAs and methylates long noncoding RNA (lncRNA) and U6 small nuclear RNA (U6 snRNA) [59,60]. The UACAGAGAA sequence is required for METTL16-mediated-methylation and the Nterminal module of METTL16 is essential for RNA binding [61,62].…”
Section: Mettl16mentioning
confidence: 99%
“…Moreover, METTL16-mediated modification at the 5 splice sites is considered as an important component of the splicing machinery [20]. Moreover, Doxtader et al showed that METTL16 regulates a key metabolite of homeostasis, S-adenosylmethionine SAM, which is a well-known DNA methylation cofactor [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to ensuring accurate quantification of starting material via the methods outlined in our protocol, we also highly encourage the use of multiple replicates when starting RNA material is limited to gain confidence in the identified m 6 A residues. Further, while the majority of m 6 A deposition in humans occurs via the METTL3/METTL14 writer complex, a subset is generated via another methyltransferase, METTL16 (Ruszkowska et al 2018;Doxtader et al 2018). In contrast to METTL3/METTL14-dependent m 6 As which are typically found within a 'DRACH' motif and often near stop codons, m 6 A modifications generated by METTL16 do not occur within a defined sequence motif and are more often found in introns and within noncoding RNAs (Ruszkowska et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This writer complex targets RNAs containing a 'DRACH' consensus sequence (where 'D' is any nucleotide but cytosine, 'R' is any purine, and 'H' is any nucleotide but guanine), with the cytosine downstream of the substrate adenine being essential for methylation (Liu et al 2014). The human methyltransferase METTL16 can also generate m 6 A modifications, though these residues do not occur within the same 'DRACH' consensus motif and only a very few substrates are known (Ruszkowska et al 2018;Doxtader et al 2018). While m 6 A modifications have been identified throughout the transcriptome, they are most-often enriched around 3' UTRs and stop codons (Meyer et al 2012;Dominissini et al 2012;Ke et al 2015).…”
Section: Introductionmentioning
confidence: 99%